Contraction of Rat Cauda Epididymis Smooth Muscle to alpha(1)-Adrenoceptor Activation Is Mediated by alpha(1A)-Adrenoceptors - Pacini, Enio S. A. [UNESP]; Castilho, Nthony C. S. [UNESP]; Hebeler-Barbosa, Flavia [UNESP]; Pupo, Andre S. [UNESP]; Kiguti, Luiz R. A. [UNESP] (Amer Soc Pharmacology Experimental Therapeutics, 2018)
The cauda epididymis (CE), the site of sperm storage until the ejaculation, is densely innervated by the sympathetic nervous system. Contraction of CE smooth muscle via alpha(1)-adrenoceptors (alpha(1)-ARs) plays a key role during the seminal emission phase of ejaculation and alpha(1)-AR antagonism has been suggested as a nonhormonal and reversible male contraceptive target. Since the alpha(1)-AR subtype mediating contraction of rat CE is not known, this study investigates the expression and role of alpha(1)-AR subtypes on the proximal and distal rat CE duct contraction to norepinephrine in vitro. Alpha(1a), alpha(1b), and alpha(1d) transcripts were detected by real-time quantitative polymerase chain reaction in proximal and distal CE segments and alpha(1a) and alpha(1d) were shown to predominate over alpha(1b). The inhibition of [H-3]prazosin specific binding to intact CE segments from proximal and distal CE by RS 100329 and 5-methylurapidil (alpha(1A)-selective) and BMY 7378 (alpha(1D)-selective) showed that alpha(1A)- and alpha(1D)-ARs are expressed at similar densities. Norepinephrine-induced contractions of CE were competitively antagonized with high affinity by RS 100329 (pK(B) approximate to 9.50) and 5-methylurapidil (pK(B) approximate to 9.0) and with low affinity by BMY 7378 (pK(B) approximate to 7.0) and the alpha(1B)-selective L-765,314 (pA(2) < 7.0), suggesting contractions are mediated by alpha(1A)-ARs. The clinically used alpha(1A/D)-ARs antagonist tamsulosin potently (pA(2) approximate to 10.0) inhibited the norepinephrine-induced CE contractions. Altogether, our results show that alpha(1A)- and alpha(1D)-ARs are expressed in the CE duct and alpha(1A)-AR is the main subtype mediating contraction to norepinephrine. Our results highlight the importance of alpha(1A)-AR in the peripheral control of ejaculation and strengthen the alpha(1)A(-)AR as a target for a nonhormonal approach to male contraception.